Shop drawing of BK-1(2F) (RFA-443_Rev B) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture; Web Structures (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.